Personal sense of coherence and posttraumatic stress symptoms among internally displaced women exposed to the Anglophone Crisis in Cameroon - Edwige Emilie Kouamen Tatto Mouandjo; Anne Wandjiru Mbwayo; Anne Muthoni Mathai; Jean-Baptiste Fotso Djemo; Houdou Seyni; Thomas Schnell; Julia Fischer; Roland Weierstall-Pust; Gesa Pust (Frontiers in Global Women's Health, 2026)
Women and girls affected by armed conflict and forced displacement are exposed to a high burden of potentially traumatic events, gendered insecurity, disrupted social networks, and barriers to mental health care. Evidence on protective psychological resources among internally displaced women in Central Africa remains limited. This study examined trauma load, personal sense of coherence (SoC), and sense of community coherence (SoCC) as predictors of posttraumatic stress disorder (PTSD) symptom severity among women internally displaced by the Anglophone Crisis in Cameroon. A sample of 133 female internally displaced persons (IDPs), aged 18 to 65 years, was recruited from two humanitarian organizations. Trauma exposure was assessed using the Life Events Checklist for DSM-5 and a crisis-specific trauma checklist; PTSD symptom severity was measured with the PTSD Checklist for DSM-5; and SoC and SoCC were assessed with validated self-report scales. Among six trauma-load indicators, self-experienced traumatic event types related to the Anglophone Crisis were the only trauma-related predictor retained in the final regression model. The final model included self-experienced Anglophone Crisis-related trauma ( β = .23, p = .009) and personal SoC ( β = −.18, p = .035), F (2, 130) = 7.41, p < .001, adjusted R 2 = .09. Using the PCL-5 screening cut-off of 31, 127 of 133 women (95.5%) met the threshold for probable PTSD. The findings do not establish causal mediation, but they support the interpretation that individual comprehensibility, manageability, and meaningfulness are clinically relevant resilience-related resources for displaced women. Interventions for female IDPs should combine trauma-focused care with strategies that strengthen individual coping and meaning-making while acknowledging that displacement can disrupt community-level protection.